Clinical and Radiological Changes of Ankle in Knee Osteoarthritis With Varus After Total Knee Arthroplasty: A Systematic Review - Feng, Zhiwei; Ma, Ming; Wang, Yaobin; Yang, Chenfei; Liu, Zhongcheng; Xia, Yayi (Frontiers in Surgery, 2021)
Background: Severe arthritic varus deformity remains challenging in total knee arthroplasty (TKA). Previous research had focused on restoring the correct limb alignment of the knee joint. But, ignored the impact of TKA on the ankle joint. Therefore, we conducted the systematic review to assess the clinical and radiological changes of the ankle joint after TKA in severe knee varus deformity. Methods: All studies were conducted a systematic search in four English databases (PubMed, Embase, Cochrane Library, and Web of Science), and four Chinese databases (CBM, VIP, CNKI and Wan fang Database). Screened literature and extracted data was independently performed by two researchers. The modified Methodological Index for non-Randomized Studies (MInORS) was used for the assessment of quality. Results: A total of 8 studies were eligible for this review, including 4 prospective and 4 retrospective studies. The TKA resulted a negative clinical effect in the ankle joint when patients experienced ankle OA. Seven studies reported the changes in the mechanical tibiofemoral angle, four studies reported the radiological changes of the hindfoot. The mean score of the MInORS was 9.8 out of 8 (9 to 11) Conclusion: As a result of the correction of the Knee osteoarthritis (KOA) with severe varus deformity following TKA, the radiological malalignment of the ankle joint were improved. But, there were still some patients who experienced increased ankle pain after undergoing TKA .Especially, if there was a residual knee varus deformity, a stiff hindfoot with varus deformity or ankle arthritis.